PRELIMINARY STUDIES ON AIR POLLUTION TOLERANCE INDEX (APTI) OF SELECTED PLANT SPECIES IN BIKANER CITY - Leela Kaur (Zibeline International, 2021)
Air Pollution Tolerance Index is used to find out the level of air pollution in any area with the help of plants. Plants are categorized as sensitive, intermediate and tolerant based on their APTI values. The present study examines the Air Pollution Tolerance Index of selected plant species in Bikaner city. The APTI of various plants have been computed with the values obtained by analysis of biochemical parameters such as pH of leaf extract, ascorbic acid content (AAC), total leaf chlorophyll content (TLC) and leaf relative water content (RWC). It was found that plant species Khejri (Prosopis cineraria), Neem (Azadiracta indica), Babul (Acacia nilotica), Ber (Ziziphus nummularia), Aak (Calotropis procera) and Peepal (Ficus religiosa) showed APTI values in the range of 30 to 100 which are tolerant to air pollution. Datura stramonium was the only species which falls under the intermediate category due to its APTI value of 21.5. It is recommended that these plants can be grown on national highways to combat air pollution in arid areas. Such plants can be used in the development of green belt.